Analisis Tren Penggunaan AI Generatif dalam Penyusunan Tugas Mahasiswa Bimbingan Konseling Universitas Halu Oleo: Penelitian - usman, Minarti; Kurnia Badu, Tri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The aims of this article is to provide an overview of the frequency and purposes of students using AI, students' perceptions of AI, and their attitudes toward AI regulation. This article adopts a descriptive quantitative approach, with the population consisting of all active students in the Guidance and Counseling Department, Faculty of Teacher Training and Education, Halu Oleo University (UHO). A sample of 63 students was selected using simple random sampling. Data were collected through an online questionnaire via Google Forms, consisting of 15 statements. The data analysis technique used was descriptive statistics. The results showed that students tend to accept and utilize AI in academic processes; however, they still face challenges related to ethics, transparency, and understanding of academic integrity. Therefore, a more structured institutional strategy is needed in the form of guidelines, training, and ethical regulations so that the use of AI in higher education can be carried out wisely, fairly, and responsibly.